The Ethical Values and Leadership Practices in Deuteronomy - Emina, Kemi Anthony (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
A search for a philosophy of leadership has to begin with ontological and epistemological questions. The former deals with what leadership is and the latter is concerned with how one can know. Hence, this work engages in exploring the meaning, scope, and nature of leadership through the methods of analysing common words and metaphors of leadership in the Old Testament, particularly the Book of Deuteronomy. In addition, the research perspectives on the nature of leadership in the area of leadership studies are discussed to arrive at a more comprehensive understanding of the characteristics and functions of leadership. This article deals with the ethical values that lay the foundation for the leadership practices in Deuteronomy. In doing so, sources of moral courage will be discussed first, as people’s personal and corporate moral courage has to originate from certain concepts, which serve as a philosophical underpinning, driving leaders in the ethical directions of leadership practices. Next, leadership with a concern for people and ethics is discussed. The crux of the philosophy of Deuteronomy is that people should choose life by obeying the law of the Lord and avoid destruction that results from disobeying the law. Hence, leadership practices are there to create life or well-being for the people. Finally, there will be a study on how ethical practices shape society, with reference to Israelite society in the context of the narratives in the Book of Deuteronomy.